Rare and Common Variants in COL4A1 in Chinese Patients With Intracerebral Hemorrhage - Xiaolu Liu; Qiong Yang; Lu Tang; Ji He; Danyang Tian; Baojun Wang; Lihong Xie; Changbao Li; Dongsheng Fan; Dongsheng Fan; Dongsheng Fan (Frontiers in Neurology, 2022)
Here, we screened the COL4A1 variants in Chinese intracerebral hemorrhage (ICH) patients to summarize the relationship between the variants and clinical characteristics. Targeted sequencing of a 65-gene panel including COL4A1 was performed to detect all the coding regions and ±10-bp splicing sites. In total, 568 patients were included. Regarding rare nonsynonymous variants with a minor allele frequency (MAF) <0.5%, 6 missense variants and five suspicious splice site variants, absent in 573 healthy controls, were found in 11 patients. The subgroup carrying rare variants did not show specific phenotype compared with non-variant carriers. For the single nucleotide polymorphism (SNP) loci with an MAF> 5%, we did not find a significant association between the allele or genotype distribution of the SNP loci and the risk of ICH. Rs3742207 was nominally associated with death at 1-year follow-up (p = 0.02027, OR 1.857, 95% CI 1.101-3.133) after adjusted by age, hypertension history, hematoma volume and recurrent ICH history. Nevertheless, after the Bonferroni correction, the association was no longer significant. In conclusion, rare nonsynonymous variants in COL4A1 were identified in 1.94% (11/568) of Chinese ICH patients, while rs3742207 maybe indicate a worse prognosis of ICH.